Implementasi Kaidah â€œLÄ MasÄga li al-IjtihÄd fÄ« Maurid al-Naá¹£â€ dalam Fikih Islam - Mangka, Jahada; Andi Muh. Taqiyuddin BN; Muh. Isra Syarif (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
The purpose of this research is to describe, explain the meaning and veracity of the rules LÄ MasÄga LilijtihÄd FÄ« Maurid al-Naá¹£, and to explain how the implementation of the rules LÄ MasÄga LilijtihÄd FÄ« Maurid al-Naá¹£. This research is qualitative, the type of research is library research and uses a normative juridical approach. The data collection method used was a literature study. The results showed that; 1) 1. The rule LÄ MasÄga LilijtihÄd FÄ« Maurid al-Naá¹£ has the meaning that it is not permissible to do ijtihad as long as there is a verse. And the function of fiqh rules, especially in this jurisprudence principle, is to explain that the law of fiqh functions to provide an interpretation of the text that it is not permissible to do ijtihad or seek the law of a problem as long as the problem is still explained in the law in the text. 2) The validity of the rules of LÄ MasÄga LilijtihÄd FÄ« Maurid al-Naá¹£ is listed in the passages of the Koran and as-Sunnah, which explains about prioritizing the commands of Allah and His Messenger before taking other laws if there is no explanation in the Shari'a. 3) The implementation of the rules of LÄ MasÄga LilijtihÄd FÄ« Maurid al-Naá¹£ (ijtihad is not allowed as long as nash is existing) is valid as long as it does not violate or contradict the nas, consensus, qiyas jaliy, the words of the 4 mazhab, and the judge's error in the legal outcome, cause, or method. So the implementation of this rule can be noticed in existing examples and this rule cannot always be implemented or implemented, because several things have been mentioned regarding the exceptions regarding this rule.